PERTANGGUNGJAWABAN PENGUSAHA KONVEKSI COSTACURTA TERHADAP KONSUMEN AKIBAT ADANYA WANPRESTASI - Rilo Permadi (Fakultas Hukum Universitas Islam Malang, 2020)
ABSTRACTThe agreement that occurs between the service provider and the service user is obliged to be obeyed and implemented. In this case in accordance with the rules in article 1234 of the Civil Code which states